2009
DOI: 10.1177/147323000903700343
|View full text |Cite
|
Sign up to set email alerts
|

Heterotopic Pancreas within Meckel's Diverticulum with Obscure then Massive Gastrointestinal Bleeding in a 12-year-old Child: Case Report and Review of the Literature

Abstract: We report a case of a 12-year-old boy with heterotopic pancreas (HP) located in a Meckel's diverticulum (MD) and presenting as obscure gastrointestinal (GI) bleeding. Upper GI endoscopy and colonoscopy did not reveal the source of the bleeding, however, capsule endoscopy revealed a space-occupying lesion in the ileum. The patient developed massive bleeding and an emergency exploratory laparotomy was performed. A congested MD was discovered 100 cm from the ileocaecal valve using intra-operative endoscopy; the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…Case reports have demonstrated that VCE is safe to use in children as young as 8 months or weighing as little as 7.9 kg. [ 11 , 12 ] The usefulness of VCE in children has been established for several small-bowel pathologies, such as Crohn's disease, [ 13 ] obscure gastrointestinal bleeding, [ 14 ] hereditary polyposis, [ 15 ] abdominal pain, and protein-losing enteropathy. [ 4 , 16 ] Furthermore, VCE is well suited for longitudinal monitoring of Crohn's disease activity in the small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports have demonstrated that VCE is safe to use in children as young as 8 months or weighing as little as 7.9 kg. [ 11 , 12 ] The usefulness of VCE in children has been established for several small-bowel pathologies, such as Crohn's disease, [ 13 ] obscure gastrointestinal bleeding, [ 14 ] hereditary polyposis, [ 15 ] abdominal pain, and protein-losing enteropathy. [ 4 , 16 ] Furthermore, VCE is well suited for longitudinal monitoring of Crohn's disease activity in the small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Un 50% tuvo cuadro de invaginación, el 30% con divertículo de Meckel, y en dos casos se realizó laparotomía exploradora sin contar con un diagnóstico preciso, solo con la presencia de dolor abdominal, vómito o distensión abdominal. En cinco casos se reportó el tipo según la clasificación histológica de Heinrich, siendo los tipos 1 y 2 los más frecuentes 5,6,[15][16][17][18][19][20] .…”
Section: Discussionunclassified
“…En un 62% se puede encontrar mucosa gástrica heterotópica, en el 6% tejido pancreático, en el 5% mucosa gástrica y pancreática, en el 2% mucosa yeyunal y en el 2% tejido de Brunner 4 . Clínicamente se puede manifestar con sangrado intestinal, dolor, oclusión intestinal o invaginación 5 . Es posible diagnosticarlo con gammagrafía con tecnecio 99 cuando existe mucosa gástrica ectópica, pero la tomografía computarizada es la que ha demostrado ser más específica mostrando una estructura tubular llena de líquido o bien imágenes de invaginación intestinal 6 .…”
unclassified
“…In children, case reports have suggested that the presence of heterotopic pancreatic mucosa within the MD has a strong correlation with intussusception 7. In a recent case series, Maazoun et al 8 reported three cases of heterotopic pancreatic tissue being present in a total of 27 children with secondary intussusception.…”
Section: Discussionmentioning
confidence: 99%